Sadd al-Dharâ’i’dalam memelihara agama dan kaitannya dengan asas keharmonian hubungan etnik - Wan Zulkifli Wan Hassan, (Universiti Kebangsaan Malaysia, 2005)
Sadd al-Dharā’i’‘ is unanimously accepted as one of the tools in protecting the values of Islam. The issue is, will practicing Sadd al-Dharā’i’ interfere the multi-ethnic harmony and the freedom of practicing other religions in our society. Furthermore will it causeany inconvenience to other religions’ helievers. This paper for the matter, will be an exploratory study on the legality of utilizing one of the usul fiqh’s evidences that is, Sadd al-Dharā’i’ as a source of hukm (legal rule) in a multi-races society. To achiere this, a deep understanding of the Sadd al-Dharā’i’‘ is crucial especially to ensure sanctity of our religion is secured without having to forsake our harmonious multiethnic and multi-religious relationship